Surface-plasmon-enhanced frequency upconversion in Pr(3+) doped tellurium-oxide glasses containing silver nanoparticles - Rai, Vineet Kumar; Menezes, Leonardo de S.; de Araujo, Cid B.; Kassab, Luciana R. P. [UNESP]; da Silva, Davinson M.; Kobayashi, Renata A. (American Institute of Physics (AIP), 2008)
A frequency upconversion process in Pr(3+) doped TeO(2)-ZnO glasses containing silver nanoparticles is studied under excitation with a nanosecond laser operating at 590 nm, in resonance with the (3)H(4)-->(1)D(2) transition. The excited Pr(3+) ions exchange energy in the presence of the nanoparticles, originating efficient conversion from orange to blue. The enhancement in the intensity of the luminescence at similar to 482 nm, corresponding to the (3)P(0)-->(3)H(4) transition, is due to the influence of the large local field on the Pr(3+) ions, which are located near the metallic nanoparticles. (C) 2008 American Institute of Physics.